Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah dan Dana Alokasi Umum Terhadap Alokasi Anggaran Belanja Modal Pada Pemerintah Daerah Provinsi Kalimantan Tengah - Waridhatul Risqiyah; Ahmad Yunani (PPJP Universitas Lambung Mangkurat, 2022)
This study has the objectives, namely (1) to know jointly (simultaneously) the effect of economic growth, local revenue, and general allocation funds on the capital expenditure budget allocation in the regional government of Central Kalimantan province; (2) to find out the most dominant factor influencing the allocation of the capital expenditure budget in the regional government of Central Kalimantan province. This research is quantitative research with secondary time series data. While the location of this research is Central Kalimantan Province. The object of this research is economic growth, locally generated revenue, general allocation funds, and capital expenditure budget allocation to the regional government of Central Kalimantan province from 2004-to 2018. The data obtained is then processed using multiple linear regression equation analysis with the help of the SPSS version 26.0 program.The results of this study show that (1) simultaneously, the variables of economic growth, locally generated revenue and general allocation funds had a significant effect on the capital expenditure budget allocation in the regional government of Central Kalimantan province from 2004-to 2018 (2) The results also show that the General Allocation Fund is the most dominant factor affecting the allocation of capital expenditures.